Comparative gene expression in cotton fibres of interspecific lines developed through tri-species (G. hirsutum, G. arboreum & G. anomalum) - Farzana Ashraf; Asif Ali Khan; Zulqurnain Khan; Nadia Iqbal; Zahid Mahmood; Abdul Ghaffar (Kuwait Journal of Science)
Development of superior quality cotton varieties is the only way to meet the demand for the fast-growing textile sector. Fifty interspecific lines were screened to select the diverse lines for expression analysis. Comparative expression and promoter analysis were carried out to comprehend the role of fibre genes (APX1, ATP Synthase, and GhMYB 25-like) in three interspecific lines (SL-19, SL-79 and SL-369) and three Gossypium species (Gossypium hirsutum, Gossypium arboreum & Gossypium anomalum). Among the interspecific lines, the maximum expression was noted in SL-19 for all fibre genes with varying levels at different fibre developmental stages while minimum fibre genes transcripts were present in SL-3.69. Among the species, maximum expression was noted in G. hirsutum while the minimum was noted in G. anomalum. The GhMYB25-like gene was involved in fibre initiation, showing its maximum expression at initial fibre development stages (0 & 5 DPA). APX1 and ATP synthase genes were involved in fibre elongation with more expression at 10 DPA & 15 DPA. Moreover, the identification of various important promoters in APX1, ATP synthase & GhMYB25-like genes was done which makes it an important tool for engineering extra-long fibre traits leading to the development of high-quality cotton varieties.